(untitled) (Central Medical College Journal, 2024)
Background: The descriptive cross-sectional study was conducted to find out the lifestyle of male adolescent in a selected high school Laksam, Cumilla. Sample size was 255 and data was collected by face to face interview using semi-structured questionnaire to collect information about the lifestyle of male adolescent. Objective: To determine the lifestyle of male adolescent of high school student. Methods: The study was a descriptive type of cross-sectional study. Study place was Joytipal Mohathero Orphanage High School, Laksam, Cumilla. Study populations were adolescent boys of school students at Joytipal Mohathero Orphanage High School. The duration of the study will be 1 (One) year from 1st January 2021 to 31st December, 2021. Initially data was collected then checked for completeness and correctness in order to exclude missing or inconsistent data. Then data was entered into the computer using Statistical Package for Social Sciences (SPSS, version-25). Then were presented using frequency table, graph and chart. Result: Out of 255 male adolescent, 136 (53.3%) were within the age group 15-17 years, among rest 66 (25.9%) respondents were within the age limit of 11-14 years, 53(20.8%) were within the age group 18-19 years respectively (Mean ±SD=1.95±0.683). Most of 172 (67.3%) of male adolescent do not have any history of illness and rest of the respondents 83 (32.5%) have history of illness in last 6 month. Most of 165 (64.7%) of male adolescent exercise every day and rest of the respondents 90 (35.3%) don’t exercise every day. Almost half 140 (54.9%) of respondents 7-8 hours’ sleep per night, 73 (28.6%) of respondents 5-6 hours’ sleep per night and 42 (16.5%) 9-10 hours’ sleep per night. Out of 255 respondents 164 (64.3%) used internet every day, 41 (16.1%) used internet more than a month, 24 (9.4%) used thrice a day, 14 (5.5%) used twice a day, 6 (2.4%) once a week and 6 (2.4%) once a month. Most 68 (26.7%) of respondents playing games on mobile, 59 (23.1%) of respondents watch you tube and other video watching site, 38 (14.9%) of respondents use social site (Facebook, twitter etc.), 31 (12.2%) listening music in the internet, 30 (11.8%) used messenger (like Facebook messenger, imo, WhatsApp etc.), 29 (11.4%) of respondents used as a web browsing. This study informed that there is healthy life style practicing among the adolescent boys. Conclusion: According to the study a vast number of adolescent were away from physical activities and in bedded into internet and were suffering from lack of sleep and others problems. Health education, making facilities available and further research is needed for the betterment of those adolescent. Central Medical College Journal Vol 7 No 2 July 2023 Page: 108-115